REPRESENTAÇÕES SOCIAIS SOBRE A EDUCAÇÃO ESPECIAL/EDUCAÇÃO INCLUSIVA: REVISÃO DA LITERATURA (2008-2018): SOCIAL REPRESENTATIONS OF SPECIAL EDUCATION/INCLUSIVE EDUCATION: LITERATURE REVIEW (2008-2018) (Revista Contexto & Educação, 2021)
This article is a systematic review of the literature on Social Representations (SR) of Special Education (SE)/Inclusive Education (IE) for the 2008-2018 period. The database was the Capes Dissertations and Theses Catalog and Qualis journals in the area of ​​Education. The search totaled 60 papers and it was possible to verify that these researches have increased in recent years, also that they have been produced in all regions of Brazil, and that they have been carried out in public, state and private universities. Most of them use a qualitative approach with field research and, for the constitution and analysis of data, they use interviews and Content Analysis. Research participants are mostly teachers in initial training and higher education professors. It was possible to verify that the research objectives address the SR of the processes involved in the inclusion of students with disabilities or the SR of the aspects that define the insertion of a SE student. The results of the surveys showed, mostly, that SR do not favor inclusion and that the main barriers are attitudinal accessibility and educational procedures. This review endorses the relevance of SR for studies on SE/IE.
Keywords: Special/Inclusive Education; Social Representations; Systematic review